General unitary TFD formulation for superstrings - Abdalla, M. C.B. [UNESP]; Gadelha, A. L. [UNESP]; Nedel, Daniel L. [UNESP] (Sissa Medialab Srl, 2004)
A generalization of the Thermo Field Dynamics (TFD) for fermionic degrees of freedom is proposed. Such a generalization follows a previous one where the SU(1,1) thermal group was used to obtain the closed bosonic string at finite temperature. The SU(2) thermal group is introduced to construct a general thermal Bogoliubov transformation to get the type IIB superstring at finite temperature.